Effect of Obesity on Gross Motor Development Among Children of Different Ages - Khalaj, Nafiseh (2010)
Gross motor skills are basis for almost all physical activities. Proper gross motor development among four and seven year old children is critical and essential. The failure to achieve gross motor skills by four years old children lead to impaired achievement of basic locomotor and object control skills. Similarly, gross motor development deficiencies in children aged seven years lead to lack of improved, smoothed and coordinated gross motor skills; and prevent children from mastering the gross motor skills. Therefore, this study was set up to determine and compare the gross motor development of obese children age four and seven years old, to find out whether any differences exists between gross motor development of obese children from different ages. This study is an Ex post facto study. The independent variables are age and obesity and dependent variable is gross motor development. Total sample size was 256 (gender; boys= 156; girls= 100), which was determined by using the Cohen (1992) sample size table. Participants were obese (n=128) and normal weight (n=128) children aged four and seven years at kindergartens (mean age; obese=55.3 months; normal weight=57.5 months) and primary schools (mean age; obese=89.6 months; normal weight=88.9 months) in Qazvin (a city in north part of Iran). TGMD-2 was used to assess gross motor development. This test evaluates 12 gross motor skills, classified as six locomotor (running, leaping, galloping, hopping, horizontal jumping and sliding) and six object control skills (striking stationary ball, kicking, dribbling, catching, overhand throwing and underhand rolling). The methods of analysis were correlation Pearson product, independent t-test and descriptive analysis. The results of the study determined that obese children have delay in their gross motor development (both locomotor and object control skills). Also, it was determined that there is a significant difference in GMQ score between obese children age four years old and obese children age seven years old; obese children who are age seven years old showed more delay in their gross motor development (both locomotor and object control skills) compare to obese children age four years old. It is important to identify gross motor development early so treatment can minimize the effect of the problem. Future studies, should attempt to find the appropriate exercise and physical activity programs according to age for obese children to improve their gross motor skills and prevent motor development delays.